Study on the Impact of Urban Consolidation Center (UCC) Usage in Yogyakarta City's Main Grocery Retailers in Terms of Transportation Cost - Setiawan, Fran; Jatiningrum, Wandhansari Sekar (SBM ITB, 2021)
Abstract. The increase in urbanization has led to a rise in of the number of vehicles in the city and the frequency of goods delivery in urban environments. The concepts of city logistics have been developed and implemented to cope with those problems in the urban freight transport system. One cooperative freight transport scheme is the urban consolidation scheme. Urban consolidation centers (UCC) have been used by some cities over the last two decades to minimize unnecessary vehicle movement, congestion, and pollution. For a company that sells fast-moving consumer goods (FMCG), business prospects in supermarkets or groceries are currently still quite promising. Yogyakarta City ranks as the 6th most populous city in Indonesia, making it one of the largest cities in the country. Since there are many citizens and students from other towns across Indonesia, many modern retail businesses operate in Yogyakarta. If each of these businesses distribute their goods from their distribution centers (DCs) to their respective retailers, the number of freight transports will be substantial, and the congestion level will increase. This study examines the benefit of a collaboration strategy in which the top four retailers in Yogyakarta use a UCC. The advantage is expressed in total transportation cost. We developed three different scenarios that will be compared. In this research, the gravity location model is used to determine the location of the UCC, and the demand allocation model is used to determine the optimum of demand allocation from the UCC. This study reveals that using a collaborative strategy using a UCC can decrease the total transportation cost of the retailers.Keywords: City logistics, urban consolidation center, location problem, gravity location model, demand allocation modelAbstrak. Peningkatan urbanisasi telah menyebabkan peningkatan jumlah kendaraan di kota dan frekuensi pengiriman barang di lingkungan perkotaan. Konsep logistik kota telah dikembangkan dan diimplementasikan untuk mengatasi masalah-masalah dalam sistem transportasi barang perkotaan. Salah satu skema angkutan barang koperasi adalah skema konsolidasi perkotaan. Urban consolidation centers (UCC) telah digunakan oleh beberapa kota selama dua dekade terakhir untuk meminimalkan pergerakan kendaraan, kemacetan, dan polusi yang tidak perlu. Bagi perusahaan yang menjual fast moving consumer goods (FMCG), prospek bisnis di supermarket atau bahan makanan saat ini masih cukup menjanjikan. Kota Yogyakarta menempati urutan ke-6 kota terpadat di Indonesia, menjadikannya salah satu kota terbesar di negara ini. Karena ada banyak warga dan mahasiswa dari kota-kota lain di seluruh Indonesia, banyak bisnis ritel modern beroperasi di Yogyakarta. Jika masing-masing bisnis ini mendistribusikan barang-barang mereka dari distribution centers (DC) ke pengecer masing-masing, jumlah transportasi barang akan sangat besar, dan tingkat kemacetan akan meningkat. Studi ini meneliti manfaat dari strategi kolaborasi dimana empat pengecer teratas di Yogyakarta menggunakan UCC. Keuntungan tersebut dinyatakan dalam total biaya transportasi. Kami mengembangkan tiga skenario berbeda yang akan dibandingkan. Dalam penelitian ini, model lokasi gravitasi digunakan untuk menentukan lokasi UCC, dan model alokasi permintaan digunakan untuk menentukan alokasi permintaan yang optimal dari UCC. Studi ini mengungkapkan bahwa strategi kolaboratif menggunakan UCC dapat mengurangi total biaya transportasi pengecer.Kata kunci: Logistik kota, urban consolidation center, masalah lokasi, model lokasi gravitasi, model alokasi permintaan